Penetapan TUOR Adat Mandailing Perspektif Hukum Islam - Dewi, Erna; Ichsan, Muhammad; Thaib, Badriah M.; Fata, Khairil (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract : The wedding feast or yuamul farah in each tradition certainly has its distensing or uniqueness that gives birth to the characteristics of each region. The traditions carried out by each tribe of the community are certainly different from one another, one of which is the phenomenon practiced in the traditional events of the Mandailing tribe of North Sumatra which is still attached to this day is the tuor tradition in the Mandailing traditional marriage. Tuor is the name of the marriage dowry in the Mandailing customary agreement. The general description of tuor is: a man is obliged to give tuor to the woman he is going to marry. Tuor is a custom that has existed for a long time. For the people of Mandailing, the practice is as a form of preserving estavet tradition, although some of them do not know the origin of this tradition before. The author's observation on the area can be said that some people agree with the existence of this tuor tradition, but it is undeniable that there are other parts of the community who contradict the practice of the tuor because it can burden the party who will carry out the marriage. The party who feels burdened is the young man who is about to get married. Because sometimes the nominal size of the tuor results in delays in the marriage procession due to economic problems. The result of this study is that the Islamic perspective related to the tour inherited by the Mandailing community is not contradictory, because it is carried out on the basis that it both have aspects of willingness between one party and another. In addition, there is also a sense of family, agreement and also a sense of sincerity between the two sides of the family. The amount of the tuor is no longer a benchmark in Islamic considerations Because the form of the agreement between the two sides became the main foundation in establishing the tour.Keywords: Tuor, Mandailing Customs, Islamic Law Abstrak Pesta perkawinan atau yuamul farah dalam setiap tradisi tentunya memliki distensing atau keunikannya yang melahirkan ciri khas masing-masing daerah. Tradisi-tradisi yang dilakukan oleh setiap suku masyarakat tentunya berbeda antara satu dengan adat lainya, salah satu di antaranya adalah fenomena yang di praktikkan dalam acara adat suku Mandailing Sumatera Utara yang masih melekat hingga saat ini adalah tradisi tuor dalam pernikahan adat Mandailing. Tuor merupakan sebutan mahar pernikahan dalam perjanjian adat Mandailing. Gambaran umum tentang tuor adalah: seorang laki-laki wajib memberikan tuor kepada perempuan yang akan dinikahinya. Tuor merupakan suatu adat yang telah ada sejak dahulu. Bagi masyarakat Mandailing, praktik tersebut adalah sebagai wujud melestarikan estavet tradisi, walaupun sebagian dari mereka tidak mengetahui asal mula adanya tradisi ini sebelumnya. Observasi penulis pada daerah tersebut dapat dikatakan bahwa sebagian masyarakat setuju dengan adanya tradisi tuor ini, namun tidak dipungkiri ada sebagian lain dari masyarakat yang kontradiksi dengan praktik tuor tersebut karena dapat membebani pihak yang akan melaksanakan perkawinan. Pihak yang merasa terbebani ini merupakan pemuda yang akan menikah. Karena terkadang besarnya nominal tuor mengakibatkan keterlambatan prosesi menikah karena ganguan ekonomi. Hasil dari penelitian ini adalah bahwa perspektif Islam terkait tour yang diwariskan oleh masyarakt Mandailing tidak bertentangan, karena dilakukan atas dasar sama-sama memiliki aspek kerelaan antara satu pihak dengan pihak lain. Selain itu juga ada rasa kekeluargaan, persetujuan dan juga rasa keikhlasan antara kedua belah pihak keluarga. Besaran tuor tersebut tidak lagi menjadi tolak ukur dalam pertimbangan Islam, karena wujud dari kesepakatan antara kedua belah pihak menjadi pondasi utama dalam menetapkan tour.Kata Kunci: Tuor, Adat Mandailing, Hukum Islam